Unemployment and the state in Britain : the means test and protest in 1930s south Wales and north-east England - Ward, Stephanie (Manchester University Press, 2013)
Unemployment and the state in Britain offers an important and original contribution to understandings of the 1930s. Through a comparative case study of south Wales and the north-east of England, the book explores the impact of the highly controversial means test, the relationship between the unemployed and the government and the nature of some of the largest protests of the interwar period. This study will appeal to students and scholars of the depression, social movements, studies of the unemployed, social policy and interwar British society.--